Nine promising heat stress tolerant maize inbred lines with desirable secondary traits and grain yield under severe heat stress - CGIAR Research Program on Maize (2019)
The study identified nine promising heat stress tolerant maize inbred lines with desirable secondary traits and grain yield under severe heat stress, which could be used as source germplasm in heat stress tolerance maize breeding program.